Microstructure and composition dependence of mechanical characteristics of nanoimprinted AlCoCrFeNi high-entropy alloys - Dinh-Quan Doan (Nature Portfolio, 2021)
Abstract Molecular dynamics is applied to explore the deformation mechanism and crystal structure development of the AlCoCrFeNi high-entropy alloys under nanoimprinting. The influences of crystal structure, alloy composition, grain size, and twin boundary distance on the mechanical properties are carefully analyzed. The imprinting load indicates that the highest loading force is in ascending order with polycrystalline, nano-twinned (NT) polycrystalline, and monocrystalline. The change in alloy composition suggests that the imprinting force increases as the Al content in the alloy increases. The reverse Hall–Petch relation found for the polycrystalline structure, while the Hall–Petch and reverse Hall–Petch relations are discovered in the NT-polycrystalline, which is due to the interactions between the dislocations and grain/twin boundaries (GBs/TBs). The deformation behavior shows that shear strain and local stress are concentrated not only around the punch but also on GBs and adjacent to GBs. The slide and twist of the GBs play a major in controlling the deformation mechanism of polycrystalline structure. The twin boundary migrations are detected during the nanoimprinting of the NT-polycrystalline. Furthermore, the elastic recovery of material is insensitive to changes in alloy composition and grain size, and the formability of the pattern is higher with a decrease in TB distance.